Secondary Conditions Among Males With Duchenne or Becker Muscular Dystrophy. (June 2017) - Latimer, Rebecca; Street, Natalie; Conway, Kristin Caspers; James, Kathy; Cunniff, Christopher; Oleszek, Joyce; Fox, Deborah; Ciafaloni, Emma; Westfield, Christina; Paramsothy, Pangaja; ,
Duchenne and Becker muscular dystrophy are X-linked neuromuscular disorders characterized by progressive muscle degeneration. Despite the involvement of multiple systems, secondary conditions among affected males have not been comprehensively described. Two hundred nine caregivers of affected males (aged 3-31 years) identified by the Muscular Dystrophy Surveillance, Tracking, and Research Network completed a mailed survey that included questions about secondary conditions impacting multiple body functions. The 5 most commonly reported conditions in males with Duchenne were cognitive deficits (38.4%), constipation (31.7%), anxiety (29.3%), depression (27.4%), and obesity (19.5%). Higher frequencies of anxiety, depression, and kidney stones were found among nonambulatory males compared to ambulatory males. Attention-deficit hyperactivity disorder (ADHD) was more common in ambulatory than nonambulatory males. These data support clinical care recommendations for monitoring of patients with Duchenne or Becker muscular dystrophy by a multidisciplinary team to prevent and treat conditions that may be secondary to the diagnosis.